Invasive Saccharomyces cerevisiae in a liver transplant patient: case report and review of infection in transplant recipients. Issue 3 (26th May 2015) - Popiel, K.Y.; Wong, P.; Lee, M.J.; Langelier, M.; Sheppard, D.C.; Vinh, D.C.
Abstract Saccharomyces cerevisiae, an ascosporogenous yeast commonly used in the production of food, is an emerging infection in immunocompromised patients. We report the case of a 60‐year‐old man whose orthotopic liver transplant was complicated by S. cerevisiae fungemia and peritoneal abscess, successfully treated with caspofungin and drainage. We also review the literature of invasive saccharomycoses in recipients of hematologic and solid organ transplants.